Vertical-crystalline Fe-doped beta-Ni oxyhydroxides for highly active and stable evolution reaction - Kim, Byeongyoon; Kabiraz, Mrinal Kanti; Lee, Jaewan; Choi, Changhyeok; Baik, Hionsuck; Jung, Yousung; Oh, Hyung-Suk; Choi, Sang-Il; Lee, Kwangyeol (Cell Press, 2021)
The layered transition metal oxyhydroxides have received increasing interest owing to the efficient energy conversion performance and material stability during the oxygen evolution reaction (OER). In particular, Fe-doped NiOOH has shown record-high OER performance in alkaline media among various catalysts. Theoretically, undercoordinated facets including Ni4+, exposed at the edges of NiOOH, were predicted to perform highly active OER. Therefore, here we suggest a rational catalyst design, a vertical-crystalline beta-Fe/NiOOH layer built on faceted Fe/Ni nanocrystals, which exposes Ni4+ sites and could improve the OER performance dramatically. Electrochemical OER tests recorded the overpotential of 210 mV at a current density of 10 mA cm(-2) GEO and stable operation for 5 days. In situ/operando and density functional theory studies revealed that the Ni valence cycle between +2 and +4 assisted by Fe dopant is the key engine that greatly accelerates OER kinetics and that the vertical-crystalline beta-Fe/NiOOH layers on Ni octahedra are stable under harsh OER conditions.